Analysis of Coliform Contamination and Detection of Escherichia coli, Salmonella sp. Bacteria in Lettuce Vegetables (Lactuca Sativa L.) at Banyuwangi Traditional Market - Mamluatul Faizah; Ervinda Yuliatin (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Lettuce (Lactuca sativa L.) is one of the most popular vegetables. The unchanged nutritional content is the reason for choosing lettuce to consume immediately. Coliform contamination exceeding the maximum human tolerance limit can cause various diseases; therefore, vegetable hygiene should be considered. This study aims to analyze the presence of Coliforms in lettuce from the Banyuwangi traditional market, with and without washing, and to detect E. coli and Salmonella spp. The method used was Most Probable Number (MPN) 5-5-5, and E. coli was detected on selective Eosin Methylene Blue Agar (EMBA) medium. In contrast, Salmonella sp. was detected on Salmonella Shigella Agar (SSA). The result of the Coliform test was obtained. MPN values on lettuce without washing (TC1 and TC2) were>2400 MPN/g, whereas those on lettuce with washing (C1 and C2) were 350 MPN/g and 46 MPN/g, respectively. Based on the results, it can be interpreted that each test sample does not meet the standard MPN value of >3 MPN/g. Detection of E. coli and Salmonella sp. yielded positive results in all test samples.